Applications of Taguchi technique with fuzzy logic to optimise an electrochemical micromachining process. (1st January 2011) - Thanigaivelan, R.; Arunachalam, R.M.; Jerald, J.; Niranjan, T.
This paper deals with the use of Taguchi technique with fuzzy logic to optimise electrochemical micromachining (EMM) process with multiple quality characteristics. The truncated cone tip electrode produced the highest machining rate and the conical with rounded tip electrode produced holes with lesser overcut. Hence, achieving higher machining rate with lesser overcut can be considered as a multi-objective optimisation problem. The machining parameters (the tool electrode tip shape, machining voltage, pulse on-time, electrolyte concentration) are optimised with considerations of the multiple performance characteristics (machining rate and overcut). The experiments were conducted in the developed EMM set-up. The experimental results reveal that the conical with rounded electrode, machining voltage of 9 V, pulse on-time of 10 ms and electrolyte concentration of 0.35 mole/l is the optimum combination for higher machining rate and lesser overcut. In addition in-depth studies have also been made to examine the influence of tool electrode tip on the overcut through SEM micrographs of machined micro-hole.